TIMP2 promotes intramuscular fat deposition by regulating the extracellular matrix in chicken - Huan-xian CUI; Na LUO; Li-ping GUO; Lu LIU; Si-yuan XING; Gui-ping ZHAO; Jie WEN (Journal of Integrative Agriculture, 2023)
The interaction between myocytes and intramuscular adipocytes is a hot scientific topic. Using a co-culture system, this study aims to investigate the regulation of intramuscular fat deposition in chicken muscle tissue through the interaction between myocyte and adipocyte and identify important intermediary regulatory factors. Our proteomics data showed that the protein expression of tissue inhibitor of metalloproteinases 2 (TIMP2) increased significantly in the culture medium of the co-culture system, and the content of lipid droplets was more in the co-culture intramuscular adipocytes. In addition, TIMP2 was significantly upregulated (P<0.01) in muscle tissue of individuals with high intramuscular fat content. Weighted gene co-expression network analysis revealed that TIMP2 was mainly involved in the extracellular matrix receptor interaction signaling pathway and its expression was significantly correlated with triglyceride, intramuscular fat, C14:0, C14:1, C16:0, C16:1, and C18:1n9C levels. Additionally, TIMP2 was co-expressed with various representative genes related to lipid metabolism (such as ADIPOQ, SCD, ELOVL5, ELOVL7, and LPL), as well as certain genes involved in extracellular matrix receptor interaction (such as COL1A2, COL4A2, COL5A1, COL6A1, and COL6A3), which are also significantly upregulated (P<0.05 or P<0.01) in muscle tissue of individuals with high intramuscular fat content. Our findings reveal that TIMP2 promotes intramuscular fat deposition in muscle tissue through the extracellular matrix receptor interaction signaling pathway.